Smart Trash Bin for Management of Garbage Problem in Society - Aldiga Rienarti Abidin; Yuda Irawan; Yesica Devis (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
Along with the times, one of the environmental problems faced today is the waste problem. Every day humans will produce waste, both industrial waste and household waste in everyday life. Garbage will become an environmental problem because it can interfere with human health, cause bad smells and even air pollution. Poor waste management causes harmful and unhealthy environmental problems. Sometimes people are reluctant when they want to dispose of garbage by opening and closing the trash can so it is feared that they will get bacteria on their hands. The problem of environmental waste can arise from waste management that unites all types of organic and inorganic waste in the same place, making it difficult to recycle waste. Another problem is that sometimes the cleaners are negligent in emptying the full trash can, so it will cause a bad smell. Based on the above problems, it is necessary to make a smart trash bin which will later be able to sort out the types of organic and inorganic waste. The lid of the trash can will open automatically when someone wants to throw out the trash and it will close automatically when it's finished taking out the trash. With the waste sorting technology, it will automatically reduce environmental pollution by waste, and facilitate waste management so that it can be recycled again. To overcome the bins that are full for too long, if the trash is full, it will automatically notify the cleaners via Telegram messages. From the test results, it can be concluded that the ultrasonic sensor can detect if someone is approaching with a maximum distance of 50 cm so that the cover can be opened automatically for 7 seconds. The servo motor can rotate the waste sorter according to the type of organic or inorganic waste based on the detection results of the capacitive proximity sensor. The telegram message has been successfully sent if the garbage condition has been fully detected through the ultrasonic sensor. LCD can display the type of organic or inorganic waste accurately.